2021
DOI: 10.1177/09544089211053063
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tensile properties of fiber metal laminates under different strain rates

Abstract: There has been an ever-going need for materials containing excellent mechanical properties, lower density, and improved fuel efficiency in the aerospace industry. To date, Fiber Metal Laminates (FMLs) are a prime choice for aerospace applications. The components of aircraft are subjected to various mechanical loadings under operating conditions; therefore, an in-depth understanding of material behavior under expected loading conditions is imperative for the meticulous design and manufacturing of these componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Whereas, Arall and Glare laminates exhibited high degree of strain rate-sensitivity. When the strain rate is the values are increased in the following patterns: 389 MPa, 411 MPa, and 475 MPa for Glare laminates (22% increase), and 253 MPa, 298 MPa 352 MPa for Arall laminates (39% increase) [7]. Asghar et al ( 2017) stated that ultimate tensile strength of sheets is related to nature of their components [8].…”
Section: Article Info Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, Arall and Glare laminates exhibited high degree of strain rate-sensitivity. When the strain rate is the values are increased in the following patterns: 389 MPa, 411 MPa, and 475 MPa for Glare laminates (22% increase), and 253 MPa, 298 MPa 352 MPa for Arall laminates (39% increase) [7]. Asghar et al ( 2017) stated that ultimate tensile strength of sheets is related to nature of their components [8].…”
Section: Article Info Abstractmentioning
confidence: 99%
“…Scanning electron microscope images and subsequent electron scattering spectrum data showed that adhesion on aluminum was much better in anodized and cured layers. Khalid et al (2022) treated their manufactured composites with surface de-greasing, mechanical abrasion, and anodizing. In order to perform mechanical characterization, uniaxial tensile tests were conducted at various strain rates.…”
Section: Article Info Abstractmentioning
confidence: 99%
“…[139] SMPs are widely praised and adopted by researchers for their ease of printability, exceptional performance, and extensive scope in 3DP. [140] SMPs transform their shape due to one of two mechanisms: the SME or the shape [127] Copyright 2022, the Author(s). Published by Elsevier).…”
Section: Temperature-based Stimulusmentioning
confidence: 99%
“…[5][6][7] The hybridisation of high-performance fibres with metals has so far been mainly limited to the macroscopic scale, involving layered combination of metal and highperformance fibres as hybrid fibre composites. [8][9][10] At the macroscopic scale, a notable technique is laminate hybridisation, where alternating layers of metal sheets and FRP are systematically combined. These composites, known as fibre-metal laminates (FMLs), include metal sheet layers together with FRPs, as seen in examples such as CARALL (carbon fibre reinforced epoxy/aluminium foil laminate), ARALL (aramid fibre reinforced epoxy/ aluminium foil laminate) and GLARE (glass fibre reinforced epoxy/aluminium foil laminate).…”
Section: Introductionmentioning
confidence: 99%